PUBLIC WELFARE MANAGEMENT OF SANGHA ADMINISTRATORS IN BANG KHONTHI DISTRICT. SAMUTSONGKHAM PROVINCE - Boonlert , Phrakhru Pramotepanyawat (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2020)
The temple is a representative of the Buddhism institute. With the Sangha Synod and the Sangha Administrative Administrator governing the Sangha and religious order in accordance with the discipline Civil law And the tradition of Thai society at all levels and levels Buddhist monk Is a monk who holds the position of governing the Sangha Is the driving force for the administration of the Sangha and Buddhism affairs to operate correctly in accordance with the 6 missions consisting of governing, religious education, welfare education Propagation of Buddhism Public facilities And the implied public welfare is to focus on the management of public welfare, which is to carry out various activities for the benefit of the organization or of individuals or groups of people. Or helping Or subsidizing locations that are in the public domain or in the general public Public welfare is therefore important as a means to help the society in various ways.